The Impact of Fear of Missing Out (FoMO) on the Socio-Economic Welfare of Gen Z from the Perspective of Maqashid Syariah - Muhammad Ryas Fatiha Kesuma; Syamsul Hilal; Fatih Fuadi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The development of digital technology has given rise to the phenomenon of Fear of Missing Out (FoMO), which is increasingly felt by Generation Z, the group most active in social media use. This study aims to analyze the impact of FoMO on the socio-economic well-being of Generation Z and examine this phenomenon from the perspective of the maqasid sharia (Islamic principles). The method used was a literature review with a descriptive qualitative approach through the analysis of various sources, including scientific journals, books, and relevant research reports. The results show that FoMO contributes significantly to the formation of consumptive behavior, increased social pressure, and weakened individual economic stability. Furthermore, FoMO also impacts mental health, such as anxiety, stress, and low life satisfaction. From the perspective of maqasid sharia, the FoMO phenomenon has the potential to conflict with the principles of hifz al-nafs (protecting the soul), hifz al-aql (protecting the mind), and hifz al-mal (protecting wealth), as it encourages behavior that imbalances needs and desires. This research emphasizes the importance of integrating Islamic values ​​such as modesty (zuhud), self-control (tahdzib an-nafs), and a focus on the welfare of others in dealing with digital social pressures. Thus, the maqashid sharia approach can be a normative solution to mitigate the negative impact of FoMO on the socioeconomic well-being of Generation Z.